Epidemiological investigation of poultry infectious in Kazakhstan (2021–2024) - Zikibayeva, Karlygash B.; Svanbayev, Asset A.; Akhmetsadykov, Nurlan N.; Kudaibergenova, Kamshat N.; Akhmetsadykova, Shynar N.; Nurolda, Ernur N.; Kydyrmanov, Aidyn I. (Frontiers in Veterinary Science, 2025)
IntroductionThis study examines the epidemiological dynamics and genetic diversity of major avian infectious diseases in Kazakhstan, including highly pathogenic avian influenza (HPAI), Newcastle disease virus (NDV), and others. Using official data, laboratory diagnostics, and surveys, we identified high prevalence rates and virulent strains, exposing gaps in vaccination coverage and biosecurity practices. Continuous monitoring, improved vaccination strategies, and robust biosecurity measures are essential to reduce disease impact and ensure sustainable poultry farming.MethodsA cross-sectional study was conducted to assess the prevalence and genetic diversity of major avian infectious diseases in Kazakhstan. Data sources included official reports, laboratory diagnostics (RT-PCR, ELISA, and sequencing), and a survey of veterinary specialists. Serum samples were analyzed to evaluate antibody responses and vaccine efficacy. Genetic and phylogenetic analyses were conducted for key pathogens, while a questionnaire provided insights into farm-level disease control practices.ResultsAnalysis of official data recorded 27 outbreaks of avian diseases in Kazakhstan from 2005 to 2023, primarily involving HPAI and NDV. Our research further identified virulent strains such as NDV genotype VII and infectious bursal disease virus (IBDV) variants linked to global lineages. Serological studies revealed widespread exposure to pathogens, including Mycoplasma gallisepticum (MG), Mycoplasma synoviae (MS), chicken anemia virus (CAV), Ornithobacterium rhinotracheale (ORT), and low-pathogenic avian influenza (LPAI) H9, underscoring deficiencies in vaccination coverage. Farm surveys also identified weaknesses in biosecurity measures and inconsistencies in vaccination protocols.DiscussionThe findings underscore the urgent need for enhanced biosecurity measures, standardized vaccination programs, and routine monitoring to mitigate the impact of avian infectious diseases. This integrated approach offers valuable insights to support evidence-based decision-making for effective poultry health management in Kazakhstan.